ANALISIS TINGKAT EFEKTIVITAS DAN KEMANDIRIAN KEUANGAN DAERAH KOTA BANDAR LAMPUNG TAHUN 2008 - 2012 - Kesuma, Berlian Jawa; Arianti, Fitrie (Diponegoro Journal of Economics, 2013)
Financial Independence is the ability of a self-financed activities in the area of governance, development and service to the people who have paid taxes and levies as a source of local revenue needed. This research objective is to analyze the financial independence year 2008-2012 City of Bandar Lampung and analyze effectiveness financial year 2008-2012 City of Bandar Lampung.These results indicate that the independence of the Fiscal Year 2008-2012 City of Bandar Lampung as measured by (1) Financial Independence ratio indicates that Bandar Lampung city is likely to have a very high financial dependence to central government or patterned instructive, viewed from the contribution of PAD is still not adequate to finance the construction of Bandar Lampung area and help the central government contribution is more dominant in local government activities. (2) The effectiveness ratio showed that the performance of the City of Bandar Lampung is very effective, judging from the target of the PAD always increasing and always be realized by both the budget each yearBandar Lampung city has not been independent in the implementation of regional autonomy. Therefore, Bandar Lampung city should be optimized the factors that affect the ability of local governments in raising revenue, particularly the public participation factors, in addition to the City of Belfast also have more taxes to maintain a highly potential area and always make a major contribution to the Revenue The original area of each fiscal year, the Street Lighting Tax and Restaurant Tax, so that local needs can be met properly.